PERBANKAN HIJAU DALAM ISLAM - Azizah Mursyidah (Institut Agama Islam Sahid (INAIS) Bogor, 2026)
This Systematic Literature Review (SLR) analyzes the evolution, practices, challenges, and opportunities of green banking from an Islamic perspective. Employing a qualitative SLR methodology and synthesizing N=20 journal publications from 2019 to 2024, the study explores relevant Shariah principles, current practices in Islamic Financial Institutions (IFIs), and challenges to sustainability implementation. Key findings indicate significant exponential growth in publications since 2024, alongside a critical academic shift from philosophical justification (such as Maqasid al-Sharia and Maslahah) toward managerial, empirical, and operational evaluation. Primary instruments identified are Green Sukuk Bonds, Green Waqaf, and the adoption of Green FinTech. Despite advancements, challenges persist, notably the tripartite trade-off between the Shariah ethical mandate, green performance, and conventional financial profitability. Operational success is found to be highly dependent on internal factors, specifically Green Intellectual Capital and enhanced employee engagement. This article asserts that the discipline's maturity requires proactive regulatory action, demanding the integration of Carbon Accountability within the Shariah monetary policy framework to ensure measurable environmental impact.